The constitution of Japan (November 3 1946),No.1000 (Tokyo, 2005)
This book provides information about the constitution of Japan (11/1946), civil code, commercial code, code of civil procedure, penal code, code of criminal procedure.
Keywords: Law; Indexes; Japan